Stjärneberg: Ett kvartsbrott i mesolitisk skärgårdsmiljö - Hagberg, Linus (In Situ Archaeologica, 2011)
In Eastern Central Sweden, two lithic traditions met during the Mesolithic. South of Östergötland, the primary raw material used in the making of tools was flint. In Östergötland and further north, quartz was the most common raw material used. Recently a small Mesolithic quartz quarry has been excavated outside the city of Linköping, in the central part of Östergötland. The site Stjärneberg, placed on a former island in the archipelago of the Litorina Sea, contained an exploited vein of quartz. The Stjärneberg site also contained other traces of a Mesolithic settlement, such as several pits and hearth pits. The hearth pits were radiocarbon dated to the Middle Mesolithic, approximately 7000 BP. Although Stjärneberg contained common elements of a settlement, the site was interpreted as a location visited primarily with the intention of extracting quartz.